2010
DOI: 10.3109/08037051.2010.532317
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mean platelet volume levels and subclinical target organ damage in newly diagnosed hypertensive patients

Abstract: Our findings suggested that MPV levels were associated with severity of subclinical TOD including; carotid atherosclerosis, left ventricular hypertrophy and renal damage, in hypertensive patients. In addition to this, MPV levels were significantly correlated with hs-CRP levels and 24-h ambulatory blood pressure measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…However, there are great differences in the extent of target organ damage among patients even with similar levels of SBP and DBP. These differences have been attributed to a dipping/non-dipping pattern of BP and BP variability by some authors [4,5,6,7,8,17]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are great differences in the extent of target organ damage among patients even with similar levels of SBP and DBP. These differences have been attributed to a dipping/non-dipping pattern of BP and BP variability by some authors [4,5,6,7,8,17]. …”
Section: Discussionmentioning
confidence: 99%
“…Subjects in whom this nocturnal reduction in BP is blunted are named non-dippers whereas the others are classified as dippers [4,5,6,7,8]. Although the association between non-dipping hypertension and end-organ damage is still controversial, numerous studies have confirmed that non-dipping profiles are closely and independently associated with adverse cardiovascular outcomes and increased target organ damage [4,5,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased MPV has been demonstrated in diabetes (3)(4)(5)(6)(7)(8)(9). There are conflicting results about the relation of MPV with diabetic nephropathy/microalbuminuria (MA) (10)(11)(12)(13)(14)(15)(16)(17), diabetic neuropathy (18)(19)(20), coronary artery disease (4,13,18,(21)(22)(23)(24)(25), and cerebrovascular disease (3)(4)(5)26) in diabetic patients. Large platelets may play a role in the development of vascular damage in DR by being more active, forcing 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, damaged vascular cells release substances that activate platelets, and increase thrombogenesis and the potential for development of adverse CV events. (12,13) In this light, it is possible to interpret the results of studies that have shown associations between increased MPV with target organ damage in patients with hypertension and diabetes, (14,15) and also in patients with acute coronary syndrome. (19,20) As in acute coronary syndrome, in which rupture of the fibrous cap allows contact of the platelets with the highly thrombogenic necrotic core, (19,20) vascular damage, caused by multiple CV risk factors, enables contact between platelets and thrombogenic substances even in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%